Evading Time and Place in Ankara: A Reading of Contemporary Urban Collective Memory Through Recent Transformations. Issue 4 (November 2019) - Sak, Segah; Senyapili, Burcu
Based on precedent theories on collective memory and urban studies, this article develops a framework of approach to contemporary urban collective memory. Understanding urban collective memory by handling people and urban space as a system provides a sociospatial perspective for critical approaches to cities. The study initially provides overviews of theoretical approaches to collective memory and city, and then puts forth constituents of urban collective memory. Based on these constituents, contemporary urban collective memory is discussed, and a framework for analyzing contemporary cities in terms of urban space and urban experience is introduced. For a clear portrayal of urban issues within the context, the introduced framework is devised through the case of Ankara, the capital city of Turkey and the inspiring force behind this study. This framework aims to present a ground to assess people's relation to urban spaces in the contemporary era.